Rawls's teaching and the "tradition" of political philosophy - Bejan, TM (Cambridge University Press, 2021)
This article explores Rawls's evolving orientation to “the tradition of political philosophy” over the course of his academic career, culminating in Justice as Fairness: A Restatement (2001). Drawing on archival material, it argues that Rawls's fascination with tradition arose out of his own pedagogical engagement with the debate around the “death of political philosophy” in the 1950s. Throughout, I highlight the significance of Rawls's teaching—beginning with his earliest lectures on social and political philosophy at Cornell, to his shifting views on “the tradition” in his published works, culminating in the increasingly contextually minded and irenic approach on display in Political Liberalism (1993) and Justice as Fairness. This neglected aspect of the “historical Rawls” offers insight into how Rawls himself might have read “John Rawls” as a figure in the history of political thought—and reveals that he spent a lot more time contemplating that question than one might think.